The integration of the arts in early childhood education and care in Finland - Cortez, Krista (2024)
This research examines the educational system in Finland and how it involves and implements the arts in early childhood education and care (ECEC). The study explores the understanding and practice of art integration from ECEC teachers’ perspectives and experiences. In addition to these perceptions, a series of observations were made to support this understanding. This qualitative study involved observations in two daycare centers in a rural and urban municipality and semi-structured interviews with five Finnish ECEC teachers. Three teachers were interviewed in the rural setting along with observations, and in the urban setting two teachers were interviewed followed with observations in one ECEC center. The data was analyzed according to thematic analysis with an inductive approach. The findings suggest that art integration is a common practice and mostly recognized by the ECEC teachers, but from a lack of knowledge with the arts proved to result in a challenge with the integrational aspects. However, arts integration did result in the learning and development in young children and a start for subject mixture. This study intends to show how the role and impact of the arts in the field of education, specifically in ECEC, would lead into the teaching of the arts and other disciplines through interdisciplinary learning methods for children as they grow and develop. This work observes a small area in art integration as it is conducted in the country of Finland, but this research could possibly inspire other curricula in other countries.